Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Florida)--Gray, lane, mutton, and yellowtail snappers. - Bortone, Stephen A. (U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.52)